Environmental Pollution And Urbanization Restoration Strategies In Karawang Regency - Arif, Rahman; Alifa Putri, Dian Ayu Lestari; Mandeli, Riso Sari; Barlian, Eri; Umar, Iswandi; Erianjoni, Erianjoni (LANGGAM: International Journal of Social Science Education, Art and Culture, 2022)
This study aims as a model and to provide information to the public about what can be done to help restore environmental and natural conditions, especially in Karawang Regency. This research was conducted by conducting a literature review or literature study on several previous studies related to environmental and social problems in Karawang Regency. The result is Karawang Regency that has a relatively high population density and is one of the industrial areas in the province of West Java, with environmental problems, such as Water Pollution, Air Pollution, B3 Waste, and Solid Waste, Natural Disasters, Damage to Land, Forest, and Soil Resources, Damage to Coastal and Marine Ecosystems, Legal Compliance and Facilitation of Environmental Disputes, Institutions, and Monitoring Facilities Environment, Institutions, and Facilities for Monitoring Environment, Waste, and Urbanization. The strategies that can be done to restore environmental conditions in Karawang Regency, among others; Environmental quality improvement; Wise exploitation of natural resources to maintain environmental harmony and balance; Development of science and technology in environmental management; Improved environmental management performance in business and industry; Creating responsive and alert community participation; Building a community that cares about the environment (green society concept); Increase the effectiveness of implementing environmental regulations; Build an environmental clearing hall; and Strategies for handling and controlling the urbanization of the family planning village.